Efeitos da ovariectomia e do treinamento resistido na função e no biomarcador mitocondrial MOTS-c do fígado e músculo esquelético de ratas: papel da mitocôndria no crosstalk entre fígado e músculo - Garcia, Christopher Barsaque (Universidade Federal de São Carlos, 2024)
Background: The hormonal decline present in menopause can lead to mitochondrial dysfunction, predisposing women to musculoskeletal and metabolic diseases including sarcopenia and non-alcoholic fatty liver disease (NAFLD). Evidence indicates that there is a crosstalk between the liver and skeletal muscle, currently targeting mitochondrial biomarkers. MOTS-c, a mitochondrial molecule released by mitochondria under stress, represents one of these markers, playing a role in regulating glucose uptake and lipid metabolism, acting in the crosstalk between the two tissues. In this context, resistance training (RT) has been shown to be effective in improving mitochondrial function and preventing/treating sarcopenia and NAFLD in menopausal women. Objective: To investigate the effects of ovariectomy and RT on mitochondrial function and the expression of the MOTS-c biomarker, involved in crosstalk between liver and skeletal muscle. Methods: 20 young adult Wistar rats were divided into 4 groups (INT-SED, INT-RT, OVX-SED and OVX-RT). Ovariectomy was performed after 13 weeks of age. RT was performed weekly (3x/week) for 20 weeks. The tissues were euthanized and collected 48 hours after the last RT session. The following analyses were carried out on liver and gastrocnemius muscle tissue biopsies: 1) Gene expression (RT-qPCR) of the electron transport chain (CTE: CI, CII, CIII, CIV and CV) and MOTS-c; 2) Oxygen consumption by High Resolution Respirometry; 3) Citrate synthase activity. Statistical analysis was performed by One-Way ANOVA followed by Fisher's Post-hoc test (p < 0.05). Results: Body mass: the OVX-SED group (357.4 ± 18.1 g) was significantly larger than the other groups; Maximum workload: both RT groups had significantly increased CMC, INT-RT (771.6 ± 3.1 g) and OVX-RT (772.2 ± 0.8 g) at the end of the experiment; Liver respirometry: decreased oxygen consumption in the OVX-SED group in S3 (CI + CII) (40.5 ± 13.3 pmol/sec*mg) compared to the other groups, and increased oxygen consumption in the RT groups (OVX-RT = 75.6 ± 23.6; INT-RT = 81.8 ± 37.6 pmol/sec*mg); Respirometry of the gastrocnemius: decreased oxygen consumption in the OVX-SED group in S3 (CI + CII) (36.3 ± 4.5 pmol/sec*mg) compared to the other groups, and increased oxygen consumption in the RT groups (OVX-RT = 49.1 ± 6.7; INT-RT = 50.5 ± 7.5 pmol/sec*mg); RT-qPCR in the liver: reduced gene expression of CIV and ATPS in the OVX-SED group (0.71 ± 0.0 and 0.71 ± 0.0 AU) compared to INT-SED, and increased CII gene expression in both RT groups (OVX-RT = 1.20 ± 0.0; INT-RT = 1.30 ± 0.3 AU), RT increased MOTS-c gene expression in both trained groups (OVX-RT = 2.29 ± 0.6; INT-RT = 2.19 ± 1.0 AU); RT-qPCR in the gastrocnemius: reduction in CIII and CIV gene expression in the OVX-SED group (0.87 ± 0.4 and 0.59 ± 0.2 UA) compared to INT-SED, and increase in CIV gene expression in both RT groups (OVX-RT = 1.49 ± 0.6; INT-RT = 1.62 ± 0.5 UA), RT increased MOTS-c gene expression in the OVX-RT group (1.26 ± 0.4 UA) compared to OVX-SED. Conclusion: Ovariectomy produced mitochondrial dysfunction in the liver and gastrocnemius, reducing gene expression of ETC and MOTS-c proteins. However, RT as a non-pharmacological intervention was effective in preventing this damage. The increased expression of the MOTS-c gene in the RT groups indicates the presence of mitochondrial biomarkers that confirm the crosstalk between liver and muscle tissues promoted by exercise.
Effects of ovariectomy and resistance training on the function and mitochondrial biomarker MOTS-c in the liver and skeletal muscle of female rats: role of mitochondria in the crosstalk between liver and muscle
Keywords: Ovariectomia; Menopausa; Disfunção mitocondrial; Crosstalk; Treinamento resistido; Ovariectomy; Menopause; Mitochondrial dysfunction; Resistance training; CIENCIAS BIOLOGICAS::FISIOLOGIA